2020
DOI: 10.1093/cid/ciaa1839
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Strategy and Rifampin on Treatment Outcome in Cutibacterium Periprosthetic Joint Infections

Abstract: Background Cutibacterium species are common pathogens in periprosthetic joint infections (PJI). These infections are often treated with β-lactams or clindamycin as monotherapy, or in combination with rifampin. Clinical evidence supporting the value of adding rifampin for treatment of Cutibacterium PJI is lacking. Materials/methods In this multicenter retrospective study, we evaluated patients with Cutibacterium PJI. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
1
32
1
Order By: Relevance
“…In general, the infection free outcome after treatment of periprosthetic joint infections due to Cutibacterium spp. is about 85%, but worse if only a debridement is performed and the implant is retained [ 68 ]. This observation indicates that these infections are biofilm-related and that removal of the periprosthetic biofilm is needed to increase success rate.…”
Section: Evidence For C Acnes Biofilms In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the infection free outcome after treatment of periprosthetic joint infections due to Cutibacterium spp. is about 85%, but worse if only a debridement is performed and the implant is retained [ 68 ]. This observation indicates that these infections are biofilm-related and that removal of the periprosthetic biofilm is needed to increase success rate.…”
Section: Evidence For C Acnes Biofilms In Vivomentioning
confidence: 99%
“…In a large multicenter study studying risk factors for Cutibacterium spp. relapses, radical surgery and a prolonged antibiotic treatment over 6 weeks led to the best outcomes and avoided relapse of infection [ 68 ]. This is yet another indication for the biofilm character of the infection, as a non-biofilm infection would be expected to heal with a shorter antibiotic treatment.…”
Section: Evidence For C Acnes Biofilms In Vivomentioning
confidence: 99%
“…Unfortunately, there is currently no gold standard for the therapy of orthopedic implant-related infections. Antibiotic therapy continues to play a vital role in the clinical treatment of orthopedic implant-related infections, usually involving systemic or local antibiotic therapy at high doses over a prolonged period [ 4 , 5 ]. However, the current antibiotic therapy is still far from satisfactory, with treatment failure rates of approximately 20% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among PJI-associated strains, six belonged to cases with a good outcome and six cases had an infection relapse ( Supplementary Table S1 ). All cases, including relapse cases, were previously treated with surgical debridement and antibiotics [ 36 ]. Infection relapse was defined when persisting signs or symptoms of infection (pain, swelling, redness, wound secretion, elevated serum inflammatory parameters) were present after surgical debridement and antibiotic treatment, and two samples from periprosthetic tissue were positive for C. acnes based on conventional culture methods.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our results revealed that C. acnes isolates from patients with treatment success and failure were genetically similar, suggesting that treatment failure might be primarily related to the choice of antibiotics and clinical management, rather than dependent on the actual causative strain [ 36 ]. Similar results were seen in a study with S. aureus strains [ 48 ], in which isolates from patients with treatment success and failure were genetically very similar, indicating that treatment failure was associated with the presence of an antimicrobial-resistant phenotype and the use of non-biofilm-active antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%